The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1007/bf00324781
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in the formation of butadiene monoxide from 1,3-butadiene

Abstract: When 1,3-butadiene is incubated with liver postmitochondrial fractions from mouse, rat, monkey or man and a NADPH-regenerating system, the formation rate of butadiene monoxide is different in the four species. With the exception of the rhesus monkey, the amount of epoxide is proportional to the monooxygenase activity. The sequence of epoxide formation is B6C3F1 mouse, Sprague Dawley rat, man, rhesus monkey. The ratio between mouse and monkey was about 7:1. When 1,3-butadiene is incubated with homogenates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…Recent studies in which BDMO formation was directly measured in vitro revealed that mouse lung microsomes activate butadiene at rates nearly 15 times greater than in rats (55). Lorenz and co-workers (56) also reported that the relative activation of butadiene by mouse lung microsomes was greater than that observed in rat lung, in agreement with studies by Schmidt and Loeser (57). In vitro hepatic activities observed from all of these groups has been greater in the mouse than in the rat.…”
Section: Pharmacokineticssupporting
confidence: 68%
“…Recent studies in which BDMO formation was directly measured in vitro revealed that mouse lung microsomes activate butadiene at rates nearly 15 times greater than in rats (55). Lorenz and co-workers (56) also reported that the relative activation of butadiene by mouse lung microsomes was greater than that observed in rat lung, in agreement with studies by Schmidt and Loeser (57). In vitro hepatic activities observed from all of these groups has been greater in the mouse than in the rat.…”
Section: Pharmacokineticssupporting
confidence: 68%
“…Considering these data, epoxide hydrolase seems to have a high capacity for butadiene monoxide which is a substrate with medium affinity. In man for liver microsomes different groups reported Vmax values between 5 and 6800 nmol/(min • mg protein) depending on the substrate (Oesch et al 1974;Glatt et al 1980;Lorenz et al 1984;Mertes et al 1985;Schmidt and Loeser 1985). The relative epoxide hydrolase capacity for butadiene monoxide in our system was therefore low.…”
Section: Liver Microsomesmentioning
confidence: 68%
“…Such a species difference has also been postulated from the in vitro and in vivo data on BU and BMO metabolism (e.g. by Schmidt and Loeser 1985;Bond et al 1986;Dahl et al 1990;Kreuzer et al 1991;Csanfidy et al 1992). The present model adds a more precise quantitative estimate, as respiratory uptake and excretion, distribution in the body, and metabolism of BU as well as BMO is incorporated.…”
Section: Discussionmentioning
confidence: 92%